Effect of Sensor-Actuator Non-collocation to Dynamic Response of Flywheel Energy Storage System Supported by Active Magnetic Bearing - Idris, Muhammad Khairi (IRC, 2016)
Because of their insane and various capabilities, Magnetic Bearing are progressively and widely being utilized as a part of various applications in different businesses. The most critical issue in utilizing Active MB is its control system which requires systems to execute and dealing with the dynamic response of rotor. A co-simulation using ADAMS and MATLAB is proposed for the dynamic simulation of high speed rotating flexible rotor supported by active magnetic bearings. A co-simulation using ADAMS and MATLAB is proposed for the dynamic simulation of high speed rotating flexible rotor supported by active magnetic bearings.